Corneal Stromal Regeneration: Current Status and Future Therapeutic Potential - Lagali, Neil (Current eye research, 2020)
The corneal stroma comprises 90% of the corneal thickness and is critical for the cornea's transparency and refractive function necessary for vision. When the corneal stroma is altered by disease, injury, or scarring, however, an irreversible loss of transparency can occur. Corneal stromal pathology is the cause of millions of cases of blindness globally, and although corneal transplantation is the standard therapy, a severe global deficit of donor corneal tissue and eye banking infrastructure exists, and is unable to meet the overwhelming need. An alternative approach is to harness the endogenous regenerative ability of the corneal stroma, which exhibits self-renewal of the collagenous extracellular matrix under appropriate conditions. To mimic endogenous stromal regeneration, however, is a challenge. Unlike the corneal epithelium and endothelium, the corneal stroma is an exquisitely organized extracellular matrix containing stromal cells, proteoglycans and corneal nerves that is difficult to recapitulate in vitro. Nevertheless, much progress has recently been made in developing stromal equivalents, and in this review the most recent approaches to stromal regeneration therapy are described and discussed. Novel approaches for stromal regeneration include human or animal corneal and/or non-corneal tissue that is acellular or is decellularized and/or re-cellularized, acellular bioengineered stromal scaffolds, tissue adhesives, 3D bioprinting and stromal stem cell therapy. This review highlights the techniques and advances that have achieved first clinical use or are close to translation for eventual therapeutic application in repairing and regenerating the corneal stroma, while the potential of these novel therapies for achieving effective stromal regeneration is discussed.